The Bourgeois Inept and the Crisis of Masculinity. Three Examples in Italian Fiction of the 1960s (ENTHYMEMA, 2024)
This article aims to analyze Alberto Moravia’s La noia (1960), Dino Buzzati’s Un amore (1963) and Alba de Céspedes’s La bambolona (1967), as three examples which, by putting the erotic obsession of a bourgeois character at the core of the narration, manage to depict the crisis of masculinity (Gunsberg). This crisis developed during the 1960s and is expressed by the character of the (sexual) inept. Firstly, I will focus on the ways in which the desire of the three protagonists is depicted. Secondly, I will study the topic of possession and its – bourgeois – forms of expression (money and marriage). Lastly, I will investigate the evolution of the three female characters (Cecilia, Laide and Ivana), who from objects of desire, detach themselves from the male gaze and become subjects of desire.
Keywords: Moravia; Buzzati; de Céspedes; Inept; Desire; Masculinities